Pengaruh good corporate governance, profitabilitas, dan ukuran perusahaan terhadap tingkat pengungkapan sustainability report - Ulfa, Romayatul Ulfa; Harjanti, Agustina Eka; Wijayanti, Sukma (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2025)
This study examines the influence of good corporate governance, profitability, and firm size on the level of sustainability report disclosure among food and beverage sector companies listed on the Indonesia Stock Exchange (IDX) for the 2022–2023 period. The audit committee and independent board of commissioners measure good corporate governance. The sample comprises 54 data points from 27 companies selected using purposive sampling. Data analysis was conducted using EViews 25. The results indicate that the audit committee does not significantly affect the disclosure of sustainability reports. Meanwhile, the independent board of commissioners, profitability, and firm size negatively and significantly affect sustainability report disclosure. These findings suggest that corporate governance practices, financial performance, and company size must be strengthened to enhance sustainability transparency.